CITRAAN DALAM KUMPULAN PUISI PERAHU KERTAS KARYA SAPARDI DJOKO DAMONO - Arnelia Trias Audiyah; Erlina Zahar; Supriyati Supriyati (Universitas Batanghari, 2022)
This study aims to describe the imagery in 12 collections of poetry Perahu Kertas by Sapardi Djoko Damono. This research belongs to qualitative descriptive research. The main data is in the form of written data in the form of quotations containing imagery elements contained in the Perahu Kertas by Sapardi Djoko Damono. The data is collected by using a literature study focused on analyzing the imagery contained in sapardi Djoko Damono's Perahu Kertas. The data analysis techniques use descriptive analysis. Based on the results of this research, it can be concluded that this image is depicted in quotations contained in 12 collections of Perahu Kertas by Sapardi Djoko Damono. The data found on five types of imagery as many as 112 data consisting of 36 vision images, 29 auditory images, 6 sniffing images, 12 touch images, and 27 motion images. The least citation found is sniffing image as many as 6 quotations. From the results of this study, it can be described that sapardi Djoko Damono's Perahu Kertas is rich of the value of literary art, using different types of imagery on its poems. This indicates that this collection of poems by Sapardi Djoko Damono is not bored to read. It brings the readers to the poems as if entering into the atmosphere of poetry created by him, which has artistic value.